Remittances and varieties of democratization in developing countries. Issue 7 (3rd October 2019) - Bastiaens, Ida; Tirone, Daniel C.
ABSTRACT: How do remittances affect democratization in developing countries? In this paper we reconcile divergent findings in the literature by examining the effect of remittances on procedural and liberal democracy in developing countries at various stages of their democratic development. Remittances are primarily sent to middle-class individuals and bypass government control. Yet, governments in countries receiving remittances want to tax this remittance income. Government officials therefore need to incentivize participation of the middle class in the formal economy by reducing the threat of expropriation. Improving procedural democracy, which assures citizens of improved property and rule of law protections, is one way to accomplish this. We argue that this relationship should only be present in mixed regime types, with the democratizing effect of remittances waning as the country's level of democracy or autocracy strengthens. Further, we expect elements of liberal democracy, such as civil rights and equality under the law, to remain unchanged in all remittance-receiving countries. The middle class and governing elite are less incentivized to improve liberal democracy to limit the power and mobilization capacity of the poor and prevent increased redistribution. We test our theory on a dataset of developing countries from 1975 through 2011.